BUILDING MOTIVATION STRATEGIES IN LEARNING ENGLISH AT PGRI SILAMPARI UNIVERSITY - Karyana Tantri (CV Grasta Glory, 2025)
This study examines the application of motivational strategies in English language learning among sixth-semester students at PGRI Silampari University. We collected data using a descriptive qualitative approach, distributing open-ended questionnaires to 22 students. The responses were analysed thematically to identify the types of motivation and teaching strategies influencing students’ learning engagement. The results revealed that instrumental motivation, such as career goals and future aspirations, was the dominant factor. Additionally, interactive teaching methods, positive reinforcement, and learner autonomy significantly increased students’ motivation. Conversely, monotonous teaching approaches were found to reduce student enthusiasm and focus. The findings emphasise the importance of applying relevant, student-centered motivational strategies to enhance English learning outcomes in higher education settings.